The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2006
DOI: 10.1007/s10488-006-0052-4
|View full text |Cite
|
Sign up to set email alerts
|

Are CAFAS Subscales and Item Weights Valid? A Preliminary Investigation of the Child and Adolescent Functional Assessment Scale

Abstract: Presents a psychometric analysis of the Child and Adolescent Functional Assessment Scale (CAFAS), one of the most commonly used measures of functional impairment in youths with emotional and behavioral disorders. Specific aims of the current investigation were to (a) examine the conceptual organization of the CAFAS items, (b) explore its scaling properties, and (c) investigate its construct validity. In Phase 1, a group of advanced graduate students and clinicians rated CAFAS items with respect to the degree t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
8
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 40 publications
0
8
0
Order By: Relevance
“…Compared with global rating scales, which provide an overall score indicating functional impairment across several domains, multidimensional scales cover different domains of functioning. They have the advantage that they include more discrete and observable variables than global scales and, as a result, are less susceptible to rater bias (Bates, Furlong, & Green, 2006), more sensitive to change over time, and of greater usefulness for prevention and treatment planning (Canino, Costello, & Angold, 1999). However, they are less cost- and time-efficient (e.g., Winters et al, 2005).…”
mentioning
confidence: 99%
“…Compared with global rating scales, which provide an overall score indicating functional impairment across several domains, multidimensional scales cover different domains of functioning. They have the advantage that they include more discrete and observable variables than global scales and, as a result, are less susceptible to rater bias (Bates, Furlong, & Green, 2006), more sensitive to change over time, and of greater usefulness for prevention and treatment planning (Canino, Costello, & Angold, 1999). However, they are less cost- and time-efficient (e.g., Winters et al, 2005).…”
mentioning
confidence: 99%
“…Functional classification systems are already standard in the field of cerebral palsy (i.e., Gross Motor Function Classification System and Manual Abilities Classification System) (Rosenbaum et al, 2014). Tools to measure functional abilities related to DDALB have been developed (Simeonsson et al, 1995;Bates et al, 2006;Greenspan and Wieder, 2008;Castro and Pinto, 2015); however, widespread practical implementation (e.g., in schools) continues to present a challenge. The exhaustiveness of the ICF itself limits applicability for this purpose (Berry and O'Connor, 2009).…”
Section: Icf As a Conceptual Framework For A Factmentioning
confidence: 99%
“…Furthermore, support for children with DDALB is not specific to medical or psychological diagnosis, but rather depends on the relationship of a child's abilities to the features of the environment (e.g., demand on functional skills, physical features, attitudes, etc.) (Bates et al, 2006;Lillvist and Granlund, 2010;Garner, 2016;Foster-Cohen and Mirfin-Veitch, 2017). For example, the label of LD does not guide specific instructional practices for an individual student (Kauffman et al, 2017).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…As with any measure of functional impairment, specific concerns with the CAFAS and GAF exist that have been detailed elsewhere (Bates, 2001; Bates, Furlong, & Green, 2006; Winters et al, 2005). For example, it has been suggested that unidimensional measures of functional impairment might equate functioning with symptomatology (Winters et al, 2005).…”
mentioning
confidence: 99%